Ethnomedicinal study of wild plants used by fringe communities in Temperate Forests of Himalayan Kashmir, India - Shaista Khan; T.H. Masoodi; M.A. Islam; A.A. Wani; A.A. Gattoo (Elsevier, 2022)
Background: This paper represents the ethnomedicinal information regarding the traditional use of wild medicinal plants in the Sindh Forest Division and its utilization to cure different ailments by fringe people which has not been fully documented. The objective of the study was to explore and document the traditional knowledge of wild plant species used by forest fringe communities of the Sindh Forest Division of Union Territory Jammu and Kashmir, India. Method: The ethnomedicinal data was collected from 111 household respondents including traditional Hakims selected by multi-stage random sampling method from the study area. With the help of a well-structured pre-tested interview schedule, data on the local (Kashmiri) names of the wild medicinal plants, their therapeutic uses, plant parts used, method of preparation and mode of administration to patients were obtained. Results: A total of 82 medicinal plant species belonging to 76 genera and 52 families were used by fringe communities to treat various ailments. Among all the medicinal plants, Artemisia absinthium shows the highest Relative Frequency of Citation value (0.89) whereas Dioscorea deltoidea possess the lowest Relative Frequency of Citation value of 0.03. Conclusion: The forest fringe communities possess abundant information on the wild medicinal plants and their specific properties for curing different diseases. This ethnomedicinal survey on the diversity and traditional knowledge of medicinal plants can provide new insights towards the discovery and development of new drugs.